An Update on Arginase Inhibitors and Inhibitory Assays - Muller, Jason; Attia, Rym; Zedet, Andy; Girard, Corine; Pudlo, Marc (Mini Reviews in Medicinal Chemistry, 2022)
Arginase, which converts arginine into ornithine and urea, is a promising therapeutic target. Arginase is involved in cardiovascular diseases, parasitic infections and through a critical role in immunity, in some cancers. There is a need to develop effective arginase inhibitors and therefore efforts to identify and optimize new inhibitors are increasing. Several methods of evaluating arginase activity are available, but few directly measure the product. Radiometric assays need to separate urea and dying reactions require acidic conditions and sometimes heating. Hence, there are a variety of different approaches available, and each approach has its own limits and benefits. In this review, we provide an update on arginase inhibitors, followed by a discussion on available arginase assays and alternative methods, focusing on the intrinsic biases and parameters that are likely to impact results.
Keywords: evaluation